PELAKSANAAN KOMUNIKASI INTERNAL DALAM KETERLIBATAN KARYAWAN DI SOHO SQUARE INDONESIA - Luh Ketut Sri Laksmi; Gracia Rachmi Adiarsi (Avant Garde, 2018)
This research discusses the activity of internal communication between Superior and Subordinate implemented by the Account Director in engaging subordinates Soho Square Indonesia to work on work and company. The purpose of this research is to understand the implementation and effect in the internal communication activities between superiors and subordinates in employee engagement at Soho Square Indonesia. The method used in this study is descriptive qualitative research method with primary and secondary data collection techniques in the form of semi structured interview with the resource person from Soho Square Indonesia. The analysis of qualitative data uses Miles and Huberman models comprising data collection, data reduction, data display and conclusion. Based on the results of the research, it was found out that the activity of internal communication between the superior and the subordinate in Soho Square Indonesia runs effectively to give impact in engaging the work of subordinates at Soho Square Indonesia.